UNITED STATES-RUSSIAN CONFLICT OVER WEALTH AND OIL IN CENTRAL ASIA AND THE CAUCASUS - Дияб аль-Ноймат, А. М.; Султан Алафрит, М.А.; Женис, Ж. (Asian Journal "Steppe Panorama", 2025)
In this article, the authors consider energy as a political force. In their article, the researchers note that from a political, economic and environmental point of view, energy security is one of the most important problems facing all countries of the world. In the study, the authors argue that in recent years, the United States, in turn, has experienced skyrocketing energy prices and geopolitical competition from Russia for energy resources, including energy security, resulting in a conflict of interest. In this case, the article clearly shows that energy security is becoming a serious problem in the world due to the rapid growth in demand for natural fuels. In fact, Central Asia and the Caucasus are the regions where the geopolitics and competition between the United States and Russia are most influenced by their vast energy resources and strategic position. The authors conclude that Central Asia and the Caucasus are of particular interest to the United States and Russia, while Central Asia and the Caucasus is one of the best options for Russia, China, and the United States.